Effect of Combination of Carbopol-940 Base and HPMC Gel Extract of Aloe Vera Flesh on Physical Properties and Antibacterial Activity of Propionibacterium acnes - Ferdy Firmansyah; Silvi Ayu Vajrika; Wildan Khairi Muhtadi (Malahayati Nursing Journal, 2022)
ABSTRACT Aloe vera (Aloe chinensis Barker.) has been shown to be efficacious as an antibacterial which has the potential to treat acne caused by the bacteria Propionibacterium acnes. The use of this combination can increase the viscosity, dissolution, diffusion, and bioavailability of the preparation. This study aims to determine the effect of the combination of Carbopol base and HPMC as a gelling agent on the physical properties and antibacterial activity of aloe vera gel against P. acnes bacteria. Aloe vera flesh extract was obtained using 70% ethanol maceration method. The gel preparation has an active substance concentration of 0.50% using a combination base of Carbopol:HPMC with a ratio of 1.00:0.50; 0.75:0.75; and 0.50:1.00. The tests included tests of adhesion, dispersibility, and viscosity as well as measurement of antibacterial activity by measuring the diameter of the inhibition zone formed on the media. The resulting data from the physical properties of the gel were analyzed by linear regression correlation. While the data on the results of the antibacterial activity were analyzed by statistical tests using the ANOVA method. The results showed that with increasing concentration of HPMC, the adhesive power and viscosity decreased, but the dispersion power increased. The three gel formulations had different zones of inhibition due to differences in diffusion that occurred in the test medium.  Keywords: Aloe Vera, Gel, Propionibacterium Acnes.